2018
DOI: 10.3892/mmr.2018.9504
|View full text |Cite
|
Sign up to set email alerts
|

Expression of long non‑coding RNA and mRNA in the hippocampus of mice with type 2 diabetes

Abstract: Long non-coding RNAs (lncRNAs) serve key roles in cell growth, development and various diseases associated with the central nervous system. However, differential expression profiles of lncRNAs in type 2 diabetes have not been reported. The present study aimed to analyze the expression pattern of lncRNA-mRNA in a type 2 diabetic mouse model using microarray analysis. The mouse model of type 2 diabetes was established and the total RNAs were extracted from the hippocampus of the mice used in the present study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In fact, most are enriched in the cytoplasm, while some are partially enriched in the nucleus or concurrently enriched in the nucleus and cytoplasm [8]. Initially, lncRNAs were viewed as "junk genes" that lack coding capacity [9]; however, they were discovered to be important in many human diseases such as diabetes, cancer, neurodegenerative diseases, cardiovascular diseases, and autoimmune diseases, such as T1DM [10,11]. LncRNAs can interact with DNA, proteins, mRNAs, miRNAs, siRNAs, and other antisense RNAs via chromatin modification [8,12], thereby acting as a bait or promoter of transcription factors [4], DNA methylation, histone modification, and genomic imprinting [13] and promoting or inhibiting translation; these interactions are involved in gene expression and regulation [14].…”
Section: Latest Development Of Lncrnasmentioning
confidence: 99%
“…In fact, most are enriched in the cytoplasm, while some are partially enriched in the nucleus or concurrently enriched in the nucleus and cytoplasm [8]. Initially, lncRNAs were viewed as "junk genes" that lack coding capacity [9]; however, they were discovered to be important in many human diseases such as diabetes, cancer, neurodegenerative diseases, cardiovascular diseases, and autoimmune diseases, such as T1DM [10,11]. LncRNAs can interact with DNA, proteins, mRNAs, miRNAs, siRNAs, and other antisense RNAs via chromatin modification [8,12], thereby acting as a bait or promoter of transcription factors [4], DNA methylation, histone modification, and genomic imprinting [13] and promoting or inhibiting translation; these interactions are involved in gene expression and regulation [14].…”
Section: Latest Development Of Lncrnasmentioning
confidence: 99%
“…A study (16) showed that the incidence of bacterial infection in DM patients was 1.2 times higher than that if healthy volunteers, and the mortality of DM patients whose blood sugar was effectively controlled was more than 2.0 times higher than that of healthy volunteers. High blood sugar level would activate various protein kinase C isoforms, which regulate the expression of nitric oxide, endothelin, nuclear transcription factor-kB, and plasminogen activator inhibitor (PAI) to affect the release of cytokines and insulin (17,18). This study also showed that thoracic patients with T2DM were accompanied by higher preoperative WBC count, suggesting activated inflammation.…”
Section: Discussionmentioning
confidence: 75%
“…To date, only a few mRNAs and lncRNAs have been reported to be dysregulated and functionally characterized in diabetic cognitive impairment. Microarray provides a comprehensive assessment of expressed probes and allows identification of mRNAs and lncRNAs with diagnostic, prognostic, and functional potential in diabetic cognitive impairment ( Ci et al, 2018 ; Santiago et al, 2019 ). To find the potential target genes of DMDD and cell signaling associated with diabetic cognitive impairment treatment, we test the gene expression profile in the hippocampi of db/db mice by RNA microarray.…”
Section: Discussionmentioning
confidence: 99%